BS ISO 11999-9. PPE for firefighters. Test methods and requirements for PPE used by firefighters who are at risk of exposure to high levels of heat and/or flame while fighting fires occurring in structures. Part 9. Firehoods (4th July 2023) - British Standards Institution,
No abstract available